2013
DOI: 10.1186/1752-153x-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (cinnamate-zinc layered hydroxide) intercalation compound for sunscreen application

Abstract: BackgroundZinc layered hydroxide (ZLH) intercalated with cinnamate, an anionic form of cinnamic acid (CA), an efficient UVA and UVB absorber, have been synthesized by direct method using zinc oxide (ZnO) and cinnamic acid as the precursor.ResultsThe resulting obtained intercalation compound, ZCA, showed a basal spacing of 23.9 Å as a result of cinnamate intercalated in a bilayer arrangement between the interlayer spaces of ZLH with estimated percentage loading of cinnamate of about 40.4 % w/w. The UV–vis absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…In addition, cinnamate anion was thermally stabilized in the interlayers of ZnLHs. 42 Mohsin et al also recently designed three UV-absorbing nanocomposites by separate intercalation of three organic UV absorbers, namely cinnamic acid (CA), benzophenone-4, and Eusolex ® 232, into Zn/Al LDHs. The study revealed that the UV-absorption range of all of the nanocomposites was longer compared to the free individual organic absorbers.…”
Section: Layered Double Hydroxides In Uv Protection and Sunscreen Formentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cinnamate anion was thermally stabilized in the interlayers of ZnLHs. 42 Mohsin et al also recently designed three UV-absorbing nanocomposites by separate intercalation of three organic UV absorbers, namely cinnamic acid (CA), benzophenone-4, and Eusolex ® 232, into Zn/Al LDHs. The study revealed that the UV-absorption range of all of the nanocomposites was longer compared to the free individual organic absorbers.…”
Section: Layered Double Hydroxides In Uv Protection and Sunscreen Formentioning
confidence: 99%
“…These organic UV absorbers undergo photodegradation under UV radiation, and the degradation products are toxic. 42 Therefore, there is a need to design new sunscreen protection formulations free from the aforementioned demerits. The photostability of these organic UV absorbers can be achieved by intercalating them with inorganic nanolayers.…”
Section: Layered Double Hydroxides In Uv Protection and Sunscreen Formentioning
confidence: 99%
“…The expanded basal spacing was attributed to the bigger size and higher density of cloprop intercalated between the interlayer of brucite-type layer compared to nitrate anions. Generally, all PXRD diffraction of cloprop-ZLH showed intercalation peak at low 2θ angle reflection through the dissociation-deposition mechanism [11,14]. All cloprop-ZLH nanocomposite produced sharp and symmetrical peaks, suggesting a well ordered stacking layer.…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
“…This is a safe herbicide system to minimize and prevent the herbicides from direct exposure to environment. Due to these properties, LDH and LMH have a huge opportunity in industrial and environmental research as absorbent [6], chemical sensor [7][8][9], catalyst [10], drug delivery [11] and controlled release formulation [12]. Co-precipitation method has been used to prepare clopropZn/Al-layered double hydroxide (cloprop-LDH), meanwhile, cloprop-zinc-layered hydroxide (cloprop-ZLH) is prepared by using a direct reaction method.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Another formulation was recently developed by intercalating an ultraviolet radiation absorbing agent (cinnammate) into zinc layered hydroxides. 27 However, its application towards fighting TB has not been well researched.…”
mentioning
confidence: 99%